USAHA PERIKANAN IKAN ASAP SELAIS DI RANTAU KOPAR KABUPATEN ROKAN HILIR PROVINSI RIAU - Ramli, M (Fakultas Perikanan dan Kelautan Universitas Riau, 2012)
The research aims: 1) to see the socio-economic situation of fishermencommunity of smoked fish processing, 2) to assess the state of smoked fishprocessing business in terms of financial, and 3) to assess whether the marketing ofsmoked fish from the Rantau Kopar still efficient. Research using survey methods.From the survey results revealed smoked fish processing businesses have long beenmade public for generations with over 10 years of business experience. Processingmost of the educational level of primary school completion only by the number ofdependents between 4-7 people. Producing processors ranging from Rp 800,000.00to Rp 1,800,000.00 per month. Smoked fish processing business needs capitalbetween Rp 460,000.00 - Rp 1,300,000.00 to the manufacturing cost of Rp900,000.00 - Rp 2,700,000.00 per week, with an average profit rate 10.98% of totalrevenue. Smoked fish marketing system from Rantau Kopar are still efficient becausethe larger fisherman share of the marketing margin.